Factors Affecting the Incidence of Low Back Pain in Cracker Micro Small and Medium Enterprises Workers - Karin, Anggie Dheana; Solikhah, Solikhah; Djannah, Sitti Nur; Sangruangake, Monthida; Turbat, Battsetseg (Universitas Ahmad Dahlan, 2024)
Background: The incidence of low back pain in past workers is increasing. Low back pain is one of the musculoskeletal obstacles characterized by the onset of pain, muscle tension, or stiffness in the region behind the abdomen from the ribs to the pelvis, with or without the spread of pain to the leg zone. The incidence of low back pain is influenced by activity period, activity weight, and age. This study intends to recognize whether there is a link between activity weight, activity period, and age with low back pain events in Micro Small, and Medium Enterprises cracker workers in Wringinagung hamlet. Method: The procedure used This research is a quantitative analytic with a cross-sectional concept. Respondents in this study amounted to 78 Micro Small and Medium Enterprises cracker workers. The instruments utilized in this study were SNQ and NRS questionnaires. Information was analyzed using the Chi-Square experiment. Result: The results obtained showed an important relationship between age (p-value=0.001), and activity period (p-value=0.001). On the other hand, the result of activity weight (p-value=0.222) means that there is no significant relationship with the incidence of low back pain in workers. Conclusion: there is an important bond between age and era of activity with the formation of low back pain in workers. There is no important relationship between the occurrence of low back pain and the weight of the activity.